Efficiency of ball manipulation in basketball players - Kocic, M.; Beric, D.; Stevanovic, M. (Facta Universitatis: Series Physical Education and Sport, 2016)
Basketball belongs to the type of sports where the skill of using one`s arms is of the greatest significance for game success. Basketball technique elements which involve the use of the ball are realized solely with the use of the arms, and this is where the name "ball manipulation" stems from. Modern basketball requires top basketball players to display the greatest level of the mentioned ability, irrespective of the playing positions within the team. The aim of this research has been to determine the situational-motor skill of a basketball player`s ball manipulation efficiency with regard to the basketball competition rank. A sample of 30 participants was analyzed, and split into two subsamples (the first subsample consisted of basketball players from the Super League, i.e. the players from the Konstantin basketball team from Nis - 15 participants, and other basketball players from the First Regional League for Men, the Junior Youth Basketball Club from Nis - 15 participants). The ball manipulation efficiency was estimated through the following tests: ball stopping, starting dribbling, ball dribbling around the body, ball dribbling through the legs and leading the ball with variants. In order to determine the inter-group differences, the Multivariate Analysis of Variance (MANOVA) was applied, while the differences between the groups were determined with the Analysis of Variance (ANOVA) for every measuring instrument separately. It was determined that the basketball players of the Super League display significantly greater values in almost all the variables, except one - ball stopping.